"Price of everything: the cost of birth,the price of death and the value of everything in between" - "Porter, Eduardo" (London, 2011)
The Price of Everything starts with a simple idea: behind every decision we make lies a price, whether that's buying a cup of coffee, taking a new job, or deciding to become a parent. Prices are the invisible thread that connect and explain our society, our economy, our culture, our mistakes and our successes. Revealing connections that are ingenious and unexpected, Eduardo Porter shows just how fundamental the price of things, work, happiness, faith, family and the future are - both to our everyday behaviour and to civilisation as we know it.
Keywords: Price